2008
DOI: 10.1177/1076029608326753
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle Surface Proteins Are Associated With Experimental Venous Thrombosis: A Preliminary Study

Abstract: SUMMARYMicroparticles (MPs) are small membrane vesicles released from activated cells and are associated with thrombosis and inflammation. Microparticles contain a unique subset of surface proteins derived from the parent cell and may be responsible for their diverse biological functions. To identify these proteins juvenile baboons (Papio anubis, n=4) underwent iliac vein thrombosis with six-hour balloon occlusion. Plasma samples were taken at baseline and at 2 days post thrombosis for MP analysis. Micropartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The role that this collection of 'minor' plasma proteins might play with respect to biocompatibility needs to be investigated to obtain a clearer picture of their functions [13,14,24]. Also, the presence of cell surface related and intercellular proteins indicates that the blood cell derived microparticles may also play a role [41,42]. The interaction of such particles with surfaces may be another contributing factor to thrombogenicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role that this collection of 'minor' plasma proteins might play with respect to biocompatibility needs to be investigated to obtain a clearer picture of their functions [13,14,24]. Also, the presence of cell surface related and intercellular proteins indicates that the blood cell derived microparticles may also play a role [41,42]. The interaction of such particles with surfaces may be another contributing factor to thrombogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, intracellular proteins such as isoforms of myosin-10, myosin-14, Arfaptin-1 and the alpha isoform of afilamin A are also found. Since we used thoroughly centrifuged platelet poor plasma for protein adsorption studies, the origins of the cytoskeletal proteins may be from microparticles derived from red blood cells, platelets and or white blood cells [41,42] which were not removed by the centrifugation and thus were available to interact with the surface (see Supplementary information). We have seen the presence of microparticles like substances in our plasma preparation.…”
Section: Plasma Protein Identification By Mass Spectrometrymentioning
confidence: 99%
“…This links both G3BP and gal-3 to inflammatory changes in VTE. In experimental VTE using four baboons, the same research group showed that fibrinogen and α 1 -anti-chymotrypsin were enriched and some immunoglobulins were down-regulated two days after a 6 h occlusion of the iliac veins [59]. G3BP was not enriched.…”
Section: Microparticle Proteomicsmentioning
confidence: 99%
“…These microvesicules are captured onto the thrombus through the interaction between P-selectin expressed on the surface of activated platelets and PSGL-1 present on microvesicules, hence delivering TF to the growing thrombus. Mice deficient in either PSGL-1 or P-selectin display thrombi with little TF and reduced thrombin generation, resulting in hampered thrombus size (Abdullah et al 2009;Morel et al 2008;Ramacciotti et al 2009). …”
Section: P-selectin/psgl-1 Couplementioning
confidence: 99%